DECISION SUPPORT SYSTEM FOR SOCIAL MEDIA ADVERTISING PROMOTION ATS POKDARIWS JONGE RAYA USING THE WEIGHTED PRODUCT METHOD - Tita Murti Cahyani; Muhammad Fairuzabadi; Puji Handayani Putri (CV. Fahr Publishing, 2024)
Promotion is a way to disseminate information about a product to consumers so that consumers are influenced to accept the product being offered. Promotion can be done by utilizing advertising on social media. However, the obstacle experienced by the Public Relations of Pokdarwis Jonge Raya in promoting managed tourism is that the promotion is only limited to using the posting feature on the social media used so that the reach of the promotion is not wide. Apart from that, there are many types of advertising on social media that have different characteristics, causing difficulties in determining which type of advertising on social media is appropriate for optimizing promotions. The Weighted Product method is a decision making method to assist in the process of selecting social media advertisements based on weighted criteria. Data was obtained through a questionnaire to 15 respondents managing Pokdarwis Jonge Raya to obtain the criteria and weights that influence promotion selection. The results of this research are a decision support system for recommending promotions for types of advertising on social media. Apart from that, there is a management information system that can manage the promotions carried out.